2014
DOI: 10.1007/s12161-014-0056-8
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Optimisation and Validation of a Method for the Separation of Five Artificial Sweeteners by UPLC-DAD in Nine Food Matrices

Abstract: A new, fast and efficient method was developed for the separation and simultaneous quantification of acesulfame-K, aspartame, cyclamate, neotame and saccharin in food by ultraperformance liquid chromatography (UPLC) and diode array detector (DAD). Univariate strategies were applied for the optimisation of mobile phase pH, proportion of solvents in the mobile phase, flow rate and column temperature. Multivariate techniques were used for the simultaneous optimisation of 13 responses applying the Derringer and Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…As regards to acesulfame, saccharin and aspartame, fortunately, none of these compounds were found in any analyzed product and these results are in accordance with the Taiwan study of Chang et al (2014). However, all the other studies found and quantified at least one sweetener in the analyzed samples of juices (Bergamo et al, 2011;Dias et al, 2015;Diogo et al, 2013;Lino et al, 2010).…”
Section: Analysis Of Real Samples and Occurrence Of Additivessupporting
confidence: 85%
See 1 more Smart Citation
“…As regards to acesulfame, saccharin and aspartame, fortunately, none of these compounds were found in any analyzed product and these results are in accordance with the Taiwan study of Chang et al (2014). However, all the other studies found and quantified at least one sweetener in the analyzed samples of juices (Bergamo et al, 2011;Dias et al, 2015;Diogo et al, 2013;Lino et al, 2010).…”
Section: Analysis Of Real Samples and Occurrence Of Additivessupporting
confidence: 85%
“…Recently, several analytical methods were employed for separation and quantification of food additives. High or ultra-high performance liquid chromatography (HPLC or UPLC) coupled to ultraviolet detector (Diogo, Silva, Pena & Lino, 2013;Lino et al, 2010), diode array detector (DAD) (Dias, Meinhart, Pane, Ballus & Godoy, 2015) have been proposed. In addition, tandem mass spectrometry (MSn) (Chang & Yeh, 2014) were the main used techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Dther authors have demonstrated that models with a slight lack of fit can still be useful to predict analytical conditions. Dias et al (2015), employed models with values of F calculated up to 10 times higher than the values of F critical , obtaining satisfactory results in the optimization of responses. Similarly, in Meinhart et al (2011) and Ballus et al (2014) studies, models with a slight lack of fit significantly contributed to the optimization of the analysis methods.…”
Section: Methods Optimization and Experimental Designmentioning
confidence: 99%
“…On this study, we also conducted experimental region restrictions to reduce the error of algorithm prediction due to the model's lack of fit, as was performed in Dias et al (2015). The experimental responses of time difference between electroosmotic flow and caffeine, indicated that the conditions of the experiments 3, 5, 7, 10, 13, 15, 16 and 17 should be avoided, since the responses were unsatisfactory (difference less than 0.25 min).…”
Section: Methods Optimization and Experimental Designmentioning
confidence: 99%
“…Generally, the beverages contain considerable amount of different sweeteners which have good solubility in water. The carbonated drinks are degassed in an ultrasonic bath, in order to remove the carbon dioxide gas that might be present in the beverage, and then the samples are simply diluted 50-to 100-fold with deionized water [33][34][35], Milli-Q water [36,37], methanol: water (8:92, v/v) [38] or (1: 1 v/v) [39], mobile phase [40] or 500 times with 0.1 % aqueous formic acid [41]. Instant products as nectars, juice, instant pudding, and sauces were solubilized in water using an ultrasonic bath for 15 min and centrifuged to separate solids [36] or add trichloroacetic acid for the precipitation of proteins, before the centrifugation and dilution [41].…”
Section: Isolation and Preconcentration Of Artificial Sweeteners Frommentioning
confidence: 99%